Analisis Pelatihan Dasar Teknik Informatika Untuk Peningkatan Dan Pengembangan Produktivitas Siswa - Ahmad Ropii Abdillah; Ayu Rizkita Agung; Faizal Akbar Supriadi; Iga Mawarni; Irvan Agustian Sugandi Putra; Imam Rifa’i; Nurul Muhtar; Muhamad Riswan; Abdullah Muhajir, S.Kom., M.Kom (AMMA : Jurnal Pengabdian Masyarakat, 2023)
This service aims to analyze the effectiveness of Informatics Engineering basic training in increasing and developing student productivity. In the era of information technology that continues to develop, a basic understanding of Informatics Engineering is becoming increasingly important for students in various fields of study and careers. However, there is still tension in the understanding and application of Informatics Engineering concepts among students.  This service includes a series of activities, including initial data collection to identify the level of understanding and application of Informatics Engineering among students, as well as developing and implementing basic training programs that suit their needs.  Thus, this service makes a positive contribution to society in increasing the understanding and application of Informatics Engineering among students. It is hoped that the increased understanding and development of Informatics Engineering skills will equip students with relevant knowledge and skills in dealing with the demands of an increasingly digital world of work.